The Effects of Drugs on Behavior Maintained by Social Contact: Role of Monoamines in Social Reinforcement - Sharp, Jessica L.; Smith, Mark A. (Frontiers in Behavioral Neuroscience, 2022)
Drug use is highly concordant among members of adolescent and young adult peer groups. One potential explanation for this observation is that drugs may increase the reinforcing effects of social contact, leading to greater motivation to establish and maintain contact with other members of the peer group. Several classes of drugs, particularly drugs that increase synaptic dopamine, increase the reinforcing effects of contextual stimuli, but the extent to which these drugs enhance the reinforcing effects of social contact is not known. The purpose of this study was to determine the extent to which drugs that increase synaptic dopamine, norepinephrine, and serotonin enhance the positive reinforcing effects of social contact. To this end, male and female Long-Evans rats were pretreated with acute doses of the selective dopamine reuptake inhibitor, WIN-35,428, the selective norepinephrine reuptake inhibitor, atomoxetine, the selective serotonin reuptake inhibitor, fluoxetine, the non-selective monoamine reuptake inhibitor, cocaine, and the non-selective monoamine releasers d-amphetamine and (±)-MDMA. Ten minutes later, the positive reinforcing effects of 30-s access to a same-sex social partner was examined on a progressive ratio schedule of reinforcement. To determine whether the reinforcement-altering effects of these drugs were specific to the social stimulus, the reinforcing effects of a non-social stimulus (30-s access to an athletic sock of similar size and coloring as another rat) was determined in control subjects. WIN-35,428, d-amphetamine, and cocaine, but not atomoxetine, fluoxetine, or MDMA, dose-dependently increased breakpoints maintained by a social partner under conditions in which responding maintained by a non-social stimulus was not affected. These data indicate that increases in extracellular dopamine, but not extracellular norepinephrine or serotonin, increases the positive reinforcing effects of social contact in both male and female rats. These data also provide support for the hypothesis that some drugs with high abuse liability increase the motivation to establish and maintain contact with social peers.